Survey of Facilities and Infrastructure for Enhancing Physical Education and Sports Capabilities at SMA 3 Boyolali. - Gilang Prayoga,; Dewangga Prada, Bajalagha; Junianto, Sefen; Panca Aji, Arya; Prabuwana Dewa, Armada; Sakti Rumpoko, Satrio (Journal of Community Capacity Empowerment, 2024)
Survey on the Facilities and Infrastructure of Physical Education, Sports, and Health at SMA Negeri 3 Boyolali." An article from the Department of Physical Education, Tunas Pembangunan University, Surakarta. This research aims to explore the condition of sports facilities and infrastructure at SMA Negeri 3 Boyolali. It is a qualitative descriptive study with the entire research subject population being the facilities and infrastructure of sports at SMA Negeri 3 Boyolali. The results indicate that the average facilities and infrastructure supporting physical education at SMA Negeri 3 Boyolali are 55%, categorized as "moderate" and meeting the standards of the teaching and learning process according to Government Regulation Number 19 of 2005 regarding National Education Standards. The overall average percentage of facilities and infrastructure is obtained by summing the averages of each sports branch divided by the total number of sports branches. Regarding sports facilities, the equipment is considered good or adequate. Out of 8 facilities, 5 (100%) are categorized as very good, including futsal, volleyball, basketball, badminton, floor gymnastics, table tennis, long jump, and sepak takraw.